Your Story: Exploring the Faith Journeys of Young Australians - Stanton, Graham (International journal of practical theology, 2025)
The Your Story research project surveyed Australian young people to explore the experiences and practices they associate with faith, spirituality, and religion. Analysis of data collected from over 400 young people aged between sixteen and twenty years who were connected to a Christian organisation identified eight faith journey narrative types and analysed factors that were either supportive of or contrary to a positive engagement with Christian faith. The study commends attending to adolescent faith as a narrative, recognising how faith is formed in a relational ecosystem, and enabling young people to activate resources by incorporating them within their stories of faith.